\(3.\left[\left(2x-1\right)^2-4\right]-14^2=7^2.5^3:175\)
\(=>3.\left[\left(2x-1\right)^2-4\right]-14^2=35\)
\(=>3.\left[\left(2x-1\right)^2-4\right]=35+14^2=35+196\)
\(=>3.\left[\left(2x-1\right)^2-4\right]=231\)
\(=>\left(2x-1\right)^2-4=231:3\)
\(=>\left(2x-1\right)^2-4=77\)
\(=>\left(2x-1\right)^2=77+4\)
\(=>\left(2x-1\right)^2=81=9^2\)
\(\Rightarrow2x-1=9\)
\(=>2x=9+1\)
\(=>2x=10\)
\(=>x=10:2\)
\(=>x=5\)
Vậy:...
# Wendy Dang
3.[(2x + 1)² - 4] - 14² = 7².5³:175
3.[(2x - 1)² - 4] - 196 = 49.125:175
3.[(2x - 1)² - 4] - 196 = 35
3.[(2x - 1)² - 4] = 35 + 196
3.[(2x - 1)² - 4] = 231
(2x - 1)² - 4 = 231 : 3
(2x - 1)² - 4 = 77
(2x - 1)² = 77 + 4
(2x - 1)² = 81
2x - 1 = 9 hoặc 2x - 1 = -9
*) 2x - 1 = 9
2x = 9 + 1
2x = 10
x = 10 : 2
x = 5 (nhận)
*) 2x - 1 = -9
2x = -9 + 1
2x = -8
x = -8 : 2
x = -4 (loại)
Vậy x = 5